EDITORIAL - Vargas, J. V. C. (Revista de Engenharia Térmica, 2003)
RETERM – Thermal Engineering is an official publication of the Brazilian Society of Mechanical Sciences (ABCM). In this fourth issue, the journal continues to be divided in two main sections: science and technology. The former is directed to publish complete articles that deal with fundamental advances in heat transfer and fluid mechanics, new physical insights, and novel experimental and analytical methods that have great appeal for the industry community, and the latter is designed to comprise informative articles that document modern engineering applications, or general advances in industry. In this issue, we continue to publish the best articles written in English language, presented at the 9th Brazilian Congress of Thermal Engineering and Sciences, ENCIT 2002, held in Caxambu, MG, from October 15th to 18th, 2002, that were selected by the Associate Technical Editors of RETERM, according to the scientific criteria of the journal. The idea is to increase the industrial and scientific impact of the research results presented in the Congress. Additional articles that have been submitted and reviewed in the regular RETERM publication process are also included in the current issue. The institutional support from the Brazilian Society of Industrial Machinery and Equipments (ABIMAQ), continues to strengthen our belief in the success of this enterprise. To open a perspective to the maintainance and continuity of RETERM, we invite the readers from the industrial community to contact our staff for subscriptions and publicity in RETERM. For the next issues we continue to welcome technical articles from both the scientific and the industrial communities to either section of RETERM, contributions to the other sections of the journal, and suggestions for new sections as well. We also welcome response and comments from our readers that will certainly help the success of RETERM.